GERAKAN HIDUP SEHAT BERBASIS HERBAL DI PANTI ASUHAN SENTOSA BANJARMASIN SEBAGAI SOLUSI PENCEGAHAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) - Mi’rajunnisa, Mi’rajunnisa; Risa Ahdyani,; Yulianita Pratiwi Indah Lestari,; Tuty Mulyani,; Nita Triadisti,; Rizka Mulya Miranti,; Nurul Fajeriyati,; Muhammad Chaidir Hafidz, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Acute Respiratory Infection (ARI) is an infection that affects the upper and lower respiratory tracts and is commonly caused by viruses or bacteria. This infection frequently occurs in children. One preventive approach to ARI is the implementation of a healthy lifestyle based on herbal practices through the utilization of medicinal plants. The purpose of this community service activity was to improve participants’ knowledge and understanding of ARI and its prevention using medicinal plants at Sentosa Orphanage, Banjarmasin. The activity was conducted through interactive counseling sessions, pre-test and post-test assessments, and question-and-answer discussions. The participants consisted of 30 children from Sentosa Orphanage, Banjarmasin. The activity was carried out smoothly and successfully, with participants showing high enthusiasm and active engagement throughout the program. The results of the pre-test and post-test indicated an improvement in participants’ understanding of herbal-based healthy lifestyle practices that can be applied for the prevention of ARI